Effectiveness of Exercise and Sex Interaction on Adipokines in Obese Rats - Putra, Made Mahaguna; Doewes, Muchsin; Purwanto, Bambang; Indarto, Dono; Idrus, Hasta Handayani (Scripta Medica, 2025)
Background/Aim: Obesity is a low-grade chronic inflammatory state that promotes a pro-inflammatory immune response. Exercise is considered to be able to prevent inflammation in obesity. The main objective was to determine the effect of the interaction between exercise and sex on inflammation and adipokine in obese rats. Methods: This research is an experiment using a factorial design with a post-test only. The subjects of this study were 30 Sprague Dawley rats. The rats were 4 months old and weighed 120 g. The rats were given a diet high in carbohydrates and fats. The measurement of obese rats used Lee’s obesity index. The obese rats were then randomly divided into six groups to be given exercise interventions. The intervention provided consisted of aerobic exercise and anaerobic exercise. The primary outcome is adiponectin, leptin, dipeptidyl peptidase-4 (DPP4), tumour necrosis factor alpha (TNF-α) and adipose tissue hypertrophy. Results: The study found that increased serum adiponectin levels were influenced by exercise (p < 0.05) and the interaction between exercise and gender (p < 0.05). Decreased serum leptin levels were influenced by gender (p < 0.05) and exercise (p < 0.05). Decreased serum DPP4 levels were influenced by exercise (p < 0.05). Decreased TNF-α expression was influenced by gender (p < 0.05) and the interaction between gender and exercise (p < 0.05). Decreased adipose cell size was influenced by gender (p < 0.05). Conclusion: This study found that aerobic exercise, anaerobic exercise and the interaction between sex and exercise significantly increased serum adiponectin and decreased TNF-α expression.